Two sisters with Mayer-Rokitansky-Küster-Hauser syndrome and serous adenocarcinoma of the ovary - Sarah P. Huepenbecker; Laura Divine; Christina S. Chu; David G. Mutch (Elsevier, 2017)
Background: Mayer-Rokitansky-Küster-Hauser syndrome is a rare entity with proposed genetic underpinnings. Ovarian carcinoma has well-described genetic associations and syndromes, although much of the etiology of the disease remains unknown. Cases: Two sisters present in the 1970s with primary amenorrhea, 46, XX karyotypes, and absent uteri consistent with MRKH syndrome. In the 2010s, both sisters again present for care. Case 1 presents one sister with stage IIIC serous ovarian adenocarcinoma and negative BRCA panel. Case No 2 presents the other sister with stage IIIC serous ovarian adenocarcinoma and a negative panel for 32 genetic variants associated with ovarian carcinoma. Conclusion: The familial association of two rare diseases and negative genetic workup could point to a new genetic understanding of reproductive structure development and ovarian carcinogenesis.